Dynamic response of high-resolution ring resonator optical spectrometers to time-varying input signals - Kalli, Kyriacos; Jackson, David A. (My University, 1995)
An analysis and experimental data of the time-dependent response of an all-fiber ring resonator in which the ring is illuminated by a phase modulated input beam are presented. The resonator is operated as a high-resolution optical-scanning spectrometer. Since the resolution limit is a function of the finesse and cavity-loop length, we will show that it is not possible to design a high-resolution ring resonator that will not produce a distorted output signal when the phase modulation rate is comparable to the response time of the ring.
Keywords: Fiber optics; Optical instruments; Phase modulation; Resonators